2013
DOI: 10.1093/cercor/bht341
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sensory Gamma Oscillations and Cross-Frequency Coupling from Childhood to Early Adulthood

Abstract: Given the importance of gamma oscillations in normal and disturbed cognition, there has been growing interest in their developmental trajectory. In the current study, age-related changes in sensory cortical gamma were studied using the auditory steady-state response (ASSR), indexing cortical activity entrained to a periodic auditory stimulus. A large sample (n = 188) aged 8-22 years had electroencephalography recording of ASSR during 20-, 30-, and 40-Hz click trains, analyzed for evoked amplitude, phase-lockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 74 publications
9
90
0
Order By: Relevance
“…Indeed, CFC has been proposed to be an effective mechanism in combining network activity with sensory processing (44)(45)(46). Significantly different CFC patterns between low-frequency rhythms and gamma rhythm were found within the S1 cortex following IoN ligations in WT, compared with KO mice (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, CFC has been proposed to be an effective mechanism in combining network activity with sensory processing (44)(45)(46). Significantly different CFC patterns between low-frequency rhythms and gamma rhythm were found within the S1 cortex following IoN ligations in WT, compared with KO mice (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, abnormalities in gamma oscillations or brain activation and connectivity involving late-maturing regions (e.g. prefrontal cortex) would not be expected to be reliably observed until later in adolescence or early adulthood in pre-schizophrenia individuals, given their protracted development [54,190]. An initial study identified deficits in the MMN response among adolescents and young adults who subsequently developed schizophrenia [191].…”
Section: Consequences Of Impaired Synaptic Plasticity In Schizophrenimentioning
confidence: 99%
“…In addition, a recent neurophysiological study demonstrated that developmental changes to brainstem components were found to continue past the age of five years (Skoe et al, 2013). Apart from functional and structural changes in development, neurochemical changes in, e.g., GABA inhibition might in part cause the observed maturational differences (Cho et al, 2013).…”
Section: Maturational Differences In Response Asymmetrymentioning
confidence: 99%
“…Differences between age groups in response amplitude at theta rates might indicate maturational changes in synaptic activity, which in turn can be the consequence of anatomical changes. Decreases and increases in white and gray matter thickness from childhood into early adulthood have been suggested to account for changes in response amplitude (Cho et al, 2013;Skoe et al, 2013). Whitford et al (2007) demonstrated that changes in neural activity follow a similar trajectory to changes in brain structure over development, with an age-related reduction in theta power mirroring an agerelated reduction in gray matter volume.…”
Section: Maturational Differences In Response Strength Neural Backgrmentioning
confidence: 99%